Students’ perception on the use of role-play to improve students’ communicative competence - Arifiana Tri Wulandari; Bambang Widi Pratolo; Rika Junianti (UAD TEFL International Conference)
Recently, speaking is important in many aspects. A technique which can be used to increase speaking skill is by using role-play. It can develop communicative competence of the students. The aim of this study is to understand the students’ problems in doing role-play and to recognize the effects of role-play for the students in communicative competence aspect. The participants were fifth semester students of English Education Department, and it included 108 students. This study was conducted in campus 4 of Universitas Ahmad Dahlan. The instruments used questionnaire and interview. In calculating the questionnaire, SPSS 17.0 was used by the researcher. The questionnaire result showed that using role-play in learning process improves the communicative competence of the students. It is supported by interview result which described that (1) using role-play can increase vocabularies of students, (2) it gives new atmosphere in the classroom, and (3) the students get some experiences to add their knowledge.